The prevalence of canine dirofilariosis in the region of Attiki - DIAKOU (Α. ΔΙΑΚΟΥ), A. (Journal of the Hellenic Veterinary Medical Society, 2018)
Blood samples of 900 dogs living in the area of Attiki (Greece) were examined. The dogs were over one year old, of different breeds, both sexes and didn't receive heartworm chemoprophylaxis or chemotherapy. All samples were examined by the modified Knott's method for the detection of microfilariae, while a serological examination (ELISA kit PetChek®, IDEXX) for the detection of parasitic antigen was performed to 552 of them. Six out of 900 (0.7%) of the samples were found positive for Dirofìlaria immitis: in 2 of them both microfilariae and parasitic antigen were detected, in 3 only parasitic antigen and in 1 sample only microfilariae were detected. The animals, in which microfilariae D. immitis were detected, were hunting dogs, often taken for hunting out of Attiki region. Moreover, in 4 of the 900 samples (0,4%) microfilariae Dirofìlaria repens were found. According to these results, the prevalence of D. immitis infection of the dog in Attiki is low. Preventive measures such as chemoprophylaxis against dirofilariosis must be taken in order to keep the infection at low level in Attiki.